Critical thinking and clinical skills by problem-based learning educational methods: an umbrella systematic review - Wei-Li Ge; Xia-Yin Zhu; Jiang-Bo Lin; Jian-Jun Jiang; Tao Li; Yi-Fei Lu; Ya-Fei Mi; Tao-Hsin Tung (BMC Medical Education)
Introduction Problem-based learning (PBL), based on self-directed learning, is an instructional strategy that shifts the approach from the instructor to the student (student-centered). Notwithstanding its adoption in undergraduate and graduate medical education, its usefulness remains a topic of debate. This study aims to review current worldwide data on the efficacy and utility of critical thinking and clinical skills using PBL educational methods for teaching programs to undergraduate medical students, ursing students, dental students and medical residents. Methods The search was conducted in June 2024 in PubMed, Cochrane, Embase, and Web of Science and included all publications regardless of the publication date, study design, or country of origin. Results Thirteen meta-analyses and systematic reviews were compiled through database screening. The results showed that PBL effectively enhanced students’ clinical skills and critical thinking abilities; nevertheless, further evidence is needed to confirm this finding. Conclusion PBL may be a successful and an effective instructional strategy, not only medical, but also nursing and dental education. Students can learn skills and acquire competencies useful for their medical professionalism through PBL in addition to their existing knowledge.